In situ diagnostics of the crystal‐growth process through neutron imaging: application to scintillators. Issue 3 (12th April 2016) - Tremsin, Anton S.; Makowska, Małgorzata G.; Perrodin, Didier; Shalapska, Tetiana; Khodyuk, Ivan V.; Trtik, Pavel; Boillat, Pierre; Vogel, Sven C.; Losko, Adrian S.; Strobl, Markus; Kuhn, L. Theil; Bizarri, Gregory A.; et al.
Abstract : The unique possibilities enabled by neutron imaging for in situ remote diagnostics of microstructural characteristics during crystal growth are demonstrated, even when the materials and surrounding structures are opaque to other more conventional interrogation techniques. Neutron radiography is implemented to image remotely the uniformity of elemental distribution ( e.g. dopant concentration) during crystal growth, the location of the liquid/solid interface and the presence of macroscopic crystal defects ( e.g. cracks), all with a temporal resolution of 5–7 s. Abstract : Neutrons are known to be unique probes in situations where other types of radiation fail to penetrate samples and their surrounding structures. In this paper it is demonstrated how thermal and cold neutron radiography can provide time‐resolved imaging of materials while they are being processed ( e.g. while growing single crystals). The processing equipment, in this case furnaces, and the scintillator materials are opaque to conventional X‐ray interrogation techniques. The distribution of the europium activator within a BaBrCl:Eu scintillator (0.1 and 0.5% nominal doping concentrations per mole) is studied in situ during the melting and solidification processes with a temporal resolution of 5–7 s. The strong tendency of the Eu dopant to segregate during the solidification process is observed in repeated cycles, with Eu forming clusters on multiple length scales (only for clusters larger than ∼50 µm, as limited by the resolution of the present experiments). It is also demonstrated that the dopant concentration can be quantified even for very low concentration levels (∼0.1%) in 10 mm thick samples. The interface between the solid and liquid phases can also be imaged, provided there is a sufficient change in concentration of one of the elements with a sufficient neutron attenuation cross section. Tomographic imaging of the BaBrCl:0.1%Eu sample reveals a strong correlation between crystal fractures and Eu‐deficient clusters. The results of these experiments demonstrate the unique capabilities of neutron imaging for in situ diagnostics and the optimization of crystal‐growth procedures.